Preferred Digital Learning Styles among Management Education Graduates in Today’s Digital Era - Sinha, Ritika; Raza, Syed Shahid (International Journal of Psychosocial Rehabilitation, 2020)
As of the traditional model, the learning paradigm has advanced to modern methods and the whole credit should be given to the advancement of the digital era. This mainly concentrates on the learner’s holistic development for encountering the challenges of the future. In providing Management programs and courses with regards to Higher Education (HE), the learning styles (LS) in addition to strategies should be integrated since the Internet as well as digital world has suffused through every society strata stimulating all sorts of changes in social, technological and economic ones. Since this world is in an express mode that is driven by technology, the future seems to be disruptive in the instance of ‘HE’ as the world is traveling from Information age to the age of experience. To adopt the original, innovative and newer LS for gratifying the learners, the ‘HE’ should embrace Information and communications technology (ICT). Rather than just providing knowledge, the assortment of digital and traditional learning would ensure skills-based learning in order to deal with the remarkable intricacy and uncertainties of this earth. By providing disparate LS in ‘HE’, the analytical ability, entrepreneurial skills, and teamwork can be built which consecutively surmount national boundaries and ameliorate the interdisciplinary learning together with life skills. The focus of this study is to explore the disparate LS in addition to strategies, which can well be integrated in teaching/learning that favour the new generation called the GenZ (people who born during the period where social media platforms, Internet, mobile devices and also other forms of digital communications is common). As a result, reinventing the course of delivering the knowledge to these students in ‘HE’ is the foremost focus that is faced in today’s Digital Era.